Facile synthesis of cyclopentenone B1- and L1-type phytoprostanes - Guy, Alexandre; Flanagan, Seamus; Durand, Thierry; Oger, Camille; Galano, Jean-Marie (Frontiers in Chemistry, 2015)
Phytoprostanes (PhytoPs) represent non-enzymatic metabolites of α-linolenic acid (ALA), the essential omega-3 polyunsaturated fatty acid (PUFA) derived from plants. PhytoPs are present in the plant kingdom and represent endogenous mediators capable of protecting cells from oxidative stress damages in plants. Recently, it was found that such metabolites are present in cooking oil in high quantities, and also that B1-PhytoPs protect immature neurons from oxidant injury and promote differentiation of oligodendrocyte progenitors through PPAR-γ activation. We report a novel and facile synthesis of natural 2,3-substituted cyclopentenone PhytoPs, 16-B1-PhytoP and 9-L1-PhytoP. Our strategy is based on reductive alkylation at the 2-position of 1,3-cyclopentanedione using a recent protocol developed by Ramachary et al., and on a cross-coupling metathesis to access conjugate dienone system. In conclusion, this strategy permitted access to B1- and L1-PhytoPs in a relative short sequence process, and afford the possibility to easily develop analogs of PhytoPs.